The Valuation of Different Island Destinations Using Gravity Models - Tomaz Dentinho; David Bedo (European Regional Science Association (ERSA), 2006)
Islands are one of the most important destinations for tourism and leisure. However, islands exhibit different levels of attractiveness in the course of time and comparing with other islands. The objective of this paper is to analyze this subject for the Archipelago of the Azores, using gravity models and the travel cost method. The study aims to understand different performances along time and between islands caused by changes in the supply side (e.g. number of hotel beds, animation activities, events, etc.). The regression analysis includes two moments: it starts with the calibration of attractiveness; in a second moment it is focused in answering the question "what affects attractiveness?". Beyond its introduction and conclusions, the study is divided into three main parts: model explanation; application of the analytical concepts for the Azores islands; and finally, the analysis of the most relevant results.
Keywords: 330